Analysis of Warehouse’s Performance (Shipping, Order Picking, Storage, Putaway, Receiving) to Achieve Effective and Efficient Performance (Financial, Productivity, Utilization, Quality, Cycle Time) - Andre Yosafat Simarmata; Juliater Simarmata (Dinasti Publisher, 2024)
Warehousing plays a pivotal role in ensuring the smooth flow of materials and spare parts to support production processes. The efficiency and reliability of warehouse operations significantly impact overall company operations, enhancing their reliability, effectiveness, and efficiency. Achieving optimal performance relies on various interconnected factors, with one crucial aspect being the enhancement of warehouse performance. Employing methodologies such as Analytical Hierarchical Process (AHP), Key Performance Indicators (KPIs), and Standard Normalization (S-NORM) aids in data processing and evaluation. For instance, PT XYZ Café Indonesia's warehouse in Jakarta utilizes 25 KPIs, divided into categories like Receiving, Putaway, Storage, Order Picking, and Shipping, each containing 5 KPIs. Analysis reveals 10 KPIs in the green category, signaling satisfactory performance, while 11 fall into the yellow category, indicating areas for improvement, and 4 are in the red category, signifying critical areas requiring immediate attention. Utilizing the S-Norm De Boer method for performance evaluation, the Jakarta warehouse achieves a performance index of 93.20335, meeting expected performance levels. However, there's a need for targeted improvements in KPIs categorized as yellow or red to enhance overall warehouse efficiency and effectiveness. Keywords : Efficient; AHP; KPI; Warehouse; Effective ; S-No